Critical Study of the Characteristics of the Judicial Decision on the Judicial Review of Supreme Court Decision Number 72 P/HUM/2022 on the Minimum Wage - Nurjannah Septyanun; Yogi Hadi Ismanto; Dwi Martini; Yulias Erwin (Jurnal Jurisprudence, 2023)
ABSTRACT  Purpose of study: This study aims to analyze the conflict of norms in the Regulation of the Minister of Manpower Number 18/2022 and Government Regulation Number 36/2022 on the Minimum Wage Determination Method. As a result of the conflict, losses will be borne by business actors on the increasing minimum wage based on Government Regulation Number 36/2021 and the Regulation of Minister of Manpower Number 18/2022. This creates legal uncertainty for business actors and laborers. Methodology: This study was conducted using the normative (doctrinal) research method with the approach of legislation and legal reasoning. Data sources were taken from primary legal materials, secondary legal materials, and tertiary legal materials using descriptive analysis and analytical critical thinking. Results: The Regulation of the Minister of Manpower contradicts the Law on Manpower in conjunction with Law on Job Creation. The conflict rose because the Manpower Law in conjunction with the Job Creation Law, has limited some of the additional advances of the Wage Determination Law to only the Government Regulation level. Special subjects are: 1) the procedure of the minimum wage regulation; and 2) the formula of the minimum wage calculation. On the judicial review, the judges declared the objection to the judicial review of the petitioner unacceptable. The lawsuit was deemed premature because the Regulation in lieu of Job Creation Law has not reached inkracht (permanent legal force). Applications of this study: This will be useful and beneficial for the development of legal science, especially aspects of legal reasoning involving court decisions. The results are also practical for businesses and laborers when using the methods of determining the legal and fair minimum wage. Novelty/Originality of this study: Judge's Legal reasoning in decision number 72 P/HUM/2022 on Minimum wage was not one of the objection points of the petitioners or the answer to them. A judicial decision outside of a lawsuit, or so-called ex parte decision, is a decision taken by the court without involving the parties to the trial. Keywords: Characteristics of Judge's Decision, Judicial Review, Minimum Wage Method  ABSTRAK  Tujuan: Untuk menganalisis pertentangan norma pada Permenaker Nomor 18/2022 dengan PP Nomor 36/2021, materi pokoknya terkait metode penetapan upah minimum. Akibat pertentangan tersebut, maka kerugian bagi pelaku usaha terhadap perbandingan kenaikan upah minimum berdasarkan PP 36/2021 dengan Permenaker 18/2022. Hal tersebut berdampak kepada ketidakpastian hukum bagi pelaku usaha dan pekerja. Metodologi: Metode penelitian normative doctrinal, dengan pendekatan Perundang-undangan, dan pendekatan penalaran hukum. Sumber data berasal dari bahan hukum primer, bahan hukum sekunder dan bahan hukum tersier. Menggunakan analisis deskriptif analitis dan critical thinking. Temuan: Ketentuan Permenaker bertentangan dengan UU Ketenagakerjaan juncto UU Cipta Kerja. Pertentangan tersebut, karena UU Ketenagakerjaan juncto UU Cipta Kerja telah membatasi beberapa pengaturan lanjutan dibawah UU terkait pengupahan hanya pada tingkat PP. Berlaku materi muatan yaitu: 1) tata cara penetapan upah minimum; dan 2) formula perhitungan upah minimum. Pada uji materiil, putusan Hakim, Menyatakan permohonan keberatan hak uji materiil dari Para Pemohon tersebut tidak dapat diterima. Gugatan dianggap masih premature, karena Perpu Cipta Kerja belum incrah. Kegunaan: Berguna dan bermanfaat bagi pengembangan ilmu hukum, khususnya aspek penalaran hukum dengan objek kajian putusan pengadilan. Berguna bagi pelaku usaha dan pekerja dalam pemilihan metode penetapan upah minimum, yang berkepastian hukum dan berkeadilan Kebaruan/Orisinalitas: Legal reasoning hakim pada putusan nomor 72 P/HUM/2022 tentang Upah Minimum, bukan merupakan salah satu poin keberatan para pemohon maupun poin jawaban dari termohon. Putusan Hakim, diluar gugatan atau disebut ex parte decision, yaitu keputusan yang diambil oleh pengadilan tanpa melibatkan para pihak dalam persidangan.   Kata Kunci: Karakteristik Putusan Hakim, Uji Materiil, Metode Upah Minimum